Mechanisms of ROS Regulation of Plant Development and Stress Responses - Huang, Honglin; Ullah, Farhan; Zhou, Dao-Xiu; Yi, Ming; Zhao, Yu (Frontiers in Plant Science, 2019)
During growth and development, plants are subjected to various environmental stress through their life cycle. ROS play an important role in maintaining plants normal growth, and improving their tolerance to stress. This review described the production and removal of ROS in plants, summarized recent progress of ROS during plant vegetative apical meristem development, organogenesis, and abiotic stress response, and some novel findings in recent years were discussed. More importantly, interplay between ROS and epigenetic modifications on gene expression regulation was specifically overviewed. To summarise, plants integrate ROS with genetic/epigenetic, hormones and external signals to further promote development and environmental adaptation.